Expansion of Psychosocial Care Centers and their relationship with health and human rights - Antonio José Correa de Pauli; Caíque Rossi Baldassarini; Janaína Cristina Pasquini de Almeida; Jaqueline Lemos de Oliveira; Regina Célia Fiorati; Carla Aparecida Arena Ventura; Jacqueline de Souza (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To analyze the factors associated with the expansion of the number of Brazilian Psychosocial Care Centers (CAPS) considering aspects related to the general health scenario and the institutionalization of human rights. Methods: An analytical document-based study, developed between February 2020 and May 2022, whose secondary data on the 27 Brazilian capitals were collected on platforms in the public domain, based on the time series from 2015 to 2020. Indicators were listed based on health system infrastructure and quality of life. For data analysis, descriptive statistics, Pearson's correlation test and Student's t test were used. Results: The capitals that expanded the number of CAPS in the analyzed period were the ones that presented the greatest political-legal framework for the protection of human rights. Conclusion: The results suggest that the greater the commitment of governments in favor of human rights, the greater the investment for CAPS expansion.